Plasmochemically prepared chitosan based biocide textile materials - Erben, Dan (2008)
The objective of this work was to plasmochemically coat a thin layer of chitosan to a suitable textile by means of coplanar discharge plasma, to design a simple and inexpensive method for testing its biocide efficiency and to realize it. The experiment was carried out with special interest in preparation of a fabric suitable as filter medium for microbiologically contaminated water. Because biofouling is a major phenomena responsible for filtration systems fouling, special attention was paid to this subject.